Increasing the Vase Life of Cut Carnation (Dianthus caryophyllus L. ‘Baltico’) by Reducing Xylem Congestion with Some Solutions - DOĞAN MERAL, Ezgi (ISPEC Tarım Bilimleri Dergisi, 2024)
Microorganisms that build up in the vase solution or in the vessels themselves can clog xylem vessels, which is one of the main reasons why cut flowers lose quality. The length of time cut flower carnations last in a vase is determined by the genotype and other chemicals. The current study was carried out at Bingol University. In order to reduce bacterial decay and extend the vase life of cut carnation (Dianthus caryophyllus L. ‘Baltico’) flowers, the purpose of this study was to compare the effects of salicylic acid (SA) at (150 mg l-1 and 250 mg l-1), thymol at (150 mg l-1 and 200 mg l-1), and 8-hydroxyquinoline citrate (8-HQC) at (150 mg l-1 and 250 mg l-1). Vase life (days), which was determined as the number of days before the flowers began to wilt, loss of flower fresh weight percentage (RFW), daily solution uptake (DSU), bacterial counts in vase solution, pigment color (L, a, b) and several chemical component tests were all evaluated at the end of the experiment. In the study, it was determined that 8-HQC at 250 mg l-1 (12,92 days) was effective on the vase life of cut carnation flowers and Salicylic acid at 250 mg l-1 concentration (12,85 days) extended the vase life by compared to the control (10,83 days), (distilled water). Simultaneously, it emerged that 8-HQC at 250 mg l-1 was beneficial for the post-harvest stress mechanisms of cut carnation flowers. 8-HQC at 250 mg l-1 increased DSU, decreased RFW loss, and decreased bacterial counts to prolong vase life.